Experiences of primary health care nurses in implementing integrated management of childhood illnesses strategy at selected clinics of Limpopo Province - E. N. Vhuromu; M. Davhana-Maselesele (AOSIS, 2009)
Treatment of the under five years is a national priority as an attempt in curbing deaths and deformities affecting children. Primary health care was implemented in the clinics in order to help in the treatment of illnesses affecting the community, including children. As a result of childhood illnesses; the World Health Organization (WHO) and United Nation Children's Fund (UNICEF) came up with Integrated Management of Childhood illnesses (IMCI) strategy to enhance treatment of such illnesses in developing countries. Primary health care nurses (PHCNS) in Limpopo province were also trained to implement the strategy. This study is intended to explore and describe the experiences of PHCNS in implementing the IMCI strategy at selected clinics in Vhembe District in the Limpopo Province. A qualitative, explorative, descriptive and contextual design was used. In-depth interviews were conducted with PHCNS who are IMCI trained and have implemented the strategy for a period of not less than two years. Data analysis was done through using Tesch's method of open coding for qualitative analysis. Findings revealed that PHCNS had difficulty in rendering IMCI services due to lack of resources and poor working conditions. Recommendations address the difficulties experienced by PHCNS when implementing the IMCI strategy.